Entrepreneurial Motivation and Challenges: A Study on Women Entrepreneurs in Sylhet City - Hani, Fathema Farjana (Global Disclosure of Economics and Business, 2015)
Women entrepreneurship is not only the way of poverty alleviation but also the key to a nation’s overall advancement. This study attempts to explore several aspects of them. It emphasized on the profile of women entrepreneurs, identifying the motivation behind their entrepreneurial career, and pinpointing the challenges they are facing. The study conducted on 50 women entrepreneurs of Sylhet city. Both primary and secondary data was used. The profile of the women entrepreneurs shows information about their age, educational qualification, marital status, type of family they belongs to. Type and ownership of their business, amount and sources of start-up capital, no. of employees and their future career plan is also included in the profile. The study identified that 31% of the respondents are self-motivated to be entrepreneurs. The reasons to start business consist of- be self-dependent, extra income for the family, to run the family business, for economic freedom, etc. The study also finds out challenges in starting and continuing business of women entrepreneurs that can obstruct the smooth functioning of it. Some of the challenges are- conservative social attitude, gender discrimination, lack of skills and training facilities, infrastructural problems, etc. The study also reveals that the women entrepreneurs in Sylhet city are getting the support of family members, and they can manage start-up capital. This study has some implication for researchers in the area of entrepreneurship and women entrepreneurship.